Employee Capabilities in Gayo Lues Regency Population and Civil Registration Services - Fatahillah*, Ridho; Bakar, Muhammad Abu; Wulandari, Florentina Ratih (Riwayat: Educational Journal of History and Humanities, 2024)
The capabilities of the state civil apparatus can provide effective services for population and civil registration in Gayo Lues Regency. The aim of this research is to analyse the capabilities of Population and Civil Registration Service employees in providing services in Gayo Lues Regency. The subjects of this research were employees in the Gayo Lues Regency Population and Civil Registration Service. The research procedure is to use qualitative methods. This research identifies supporting and inhibiting factors in increasing employee capabilities. Research Results are Research results show that there are several challenges, including a lack of human resources and facilities, which affect the quality of service. Recommendations are provided to increase service capacity and efficiency through employee training and infrastructure improvements. The service experienced by the informant proves that the capability of the Population and Civil Registration Service in Gayo Lues Regency can be said to be good. ASN capabilities in the Population and Civil Registration Service are very closely related to the quality of public services. covers various aspects such as employee qualifications and skills, infrastructure, technology and policy procedures, providing faster and more efficient services such as in terms of issuing Population documents and recording important events such as births, deaths and marriages of employees at DISDUKCAPIL Gayo Lues has a high level of honesty (rating 5) with the indicator of always reporting the results of his work to his superiors according to the actual situation. Conduct technical training regarding population administration information systems, use of new software and management of population data. Carrying out excellent service training, namely training on how to provide effective and efficient services to the community, including good communication and handling complaints from the community.